Targeting CD155 on Myeloid Derived Suppressor Cells to Prevent Postoperative Immunosuppression in Cancer Patients - Martel, André Bernard (Université d'Ottawa / University of Ottawa, 2020)
Surgery, although required to treat most solid cancers, can increase tumour seeding and metastases. We have previously shown that surgery-induced myeloid derived suppressor cells (Sx-MDSCs) play an important role in this process by directly suppressing NK cells. The Sx- MDSCs increase significantly immediately after surgery but the exact mechanism by which Sx-MDSCs suppress NK cells is still unknown. In this work, we have discovered that CD155 poliovirus receptor is significantly and specifically upregulated on Sx-MDSCs following surgical stress but is minimally expressed on other immune cells. We also demonstrate that blocking CD155 in vivo leads to an improved NK cell phenotype, measured by DNAM-1 and NKG2D, and increased NK cytotoxicity. Additionally, ex vivo CD155 blockade significantly decreases the suppressive effect of Sx-MDSCs in cancer patients. Expansion of CD155 on Sx- MDSCs could be responsible for the profound postoperative NK cell suppression, which makes it a very appealing perioperative target for immunotherapy.
Keywords: Perioperative; Cancer; Immunology; Surgery